Pendidikan Kesehatan Terhadap Peningkatan Pengetahuan Ibu Hamil Tentang Hipertensi : Health Education to Improve Pregnant Women's Knowledge About Hypertension - Venny Thrissia Regitha Cahya; Masruroh (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2025)
Hypertension in pregnancy is one of the leading causes of maternal mortality in both Indonesia and globally. In the working area of UPTD Sekatak Public Health Center, the number of hypertensive cases among pregnant women has increased over the past three years, with one recorded maternal death due to eclampsia. Preliminary studies showed that most pregnant women did not understand the signs, risks, and prevention of pregnancy-induced hypertension. This low level of knowledge indicates the need for structured educational interventions. This study aimed to determine the effect of health education on increasing pregnant women's knowledge about hypertension in the working area of UPTD Sekatak Health Center. Methods: This was a quantitative study using a pre-experimental one-group pretest-posttest design. The sample consisted of 20 pregnant women selected by purposive sampling. The intervention was conducted through individual counseling using a leaflet as the educational medium. Knowledge was measured before and after the intervention using a validated questionnaire. Data were analyzed using the Wilcoxon Signed Rank Test due to non-normal data distribution. Results: The results of the study showed a value of Z = -3.945 with p < 0.001 (p < 0.05), which means that there is a significant influence of health education on increasing pregnant women's knowledge about hypertension in the UPTD area of the Sekatak Community Health Center. Conclusion Individual health education using leaflets has been proven to be effective in increasing knowledge, so it is recommended to be implemented routinely in antenatal care as an effort to prevent pregnancy complications. ABSTRAK Hipertensi dalam kehamilan merupakan salah satu penyebab utama kematian ibu di Indonesia dan dunia. Di wilayah kerja UPTD Puskesmas Sekatak, kasus hipertensi pada ibu hamil mengalami peningkatan dalam tiga tahun terakhir, bahkan tercatat satu kasus kematian akibat eklamsia. Studi pendahuluan menunjukkan bahwa sebagian besar ibu hamil belum memahami tanda, risiko, dan cara pencegahan hipertensi dalam kehamilan. Rendahnya tingkat pengetahuan ini menunjukkan perlunya upaya edukatif yang terstruktur. Tujuan penelitian ini untuk mengetahui pengaruh pendidikan kesehatan terhadap peningkatan pengetahuan ibu hamil tentang hipertensi di Wilayah UPTD Puskesmas Sekatak. Metode penelitian ini adalah kuantitatif dengan desain pre-eksperimental one group pretest-posttest. Sampel berjumlah 20 ibu hamil yang dipilih secara purposive. Intervensi dilakukan melalui konseling individu menggunakan leaflet sebagai media edukasi. Pengukuran pengetahuan dilakukan sebelum dan sesudah intervensi menggunakan kuesioner yang telah divalidasi. Analisis data menggunakan uji Wilcoxon karena data tidak berdistribusi normal. Hasil penelitian menunjukkan nilai Z = -3,945 dengan p < 0,001 (p < 0,05), yang berarti terdapat pengaruh signifikan pendidikan kesehatan terhadap peningkatan pengetahuan ibu hamil tentang hipertensi di wilayah UPTD Puskesmas Sekatak. Pendidikan kesehatan individual dengan media leaflet terbukti efektif meningkatkan pengetahuan, sehingga direkomendasikan untuk diterapkan secara rutin dalam layanan antenatal sebagai upaya pencegahan komplikasi kehamilan.